ABOUT THE POSSIBILITY FOR MEDICAL UNIVERSITIES TO ENTER WORLD UNIVERSITY RANKINGS - V. V. Fursov (Russian State Vocational Pedagogical University, 2017)
Introduction. Leading ranking positions of the Russian higher education institutions in the world university rankings is designated as one of the priorities of the Russian universities in the concept of modernization of the Russian higher professional education. The aim of the present investigation is to examine the questions about the possibility of medical universities to enter world university rankings. Methodology and research methods. The methods involve comparative analysis of indicators of publication academic activity of higher education institutions realizing programs of training of students for medical specialties. The methods of synthesis and generalization are applied. Results and scientific novelty. A set of indicators determined by the characteristics of global rankings of universities THE, QS, ARWU helped to find out the potential and recourses of the leading Moscow medical universities to enter these rankings in terms of the volume of scientific publications in Scopus and WoS. Practical significance. The article may have practical value for the management of universities, specialists and researchers in the field of scientometrics, and students and teachers having been interested in academic mobility.